Synergetic effect of adsorption on degradation of malachite green dye under blue LED irradiation using spiral‐shaped photocatalytic reactor. Issue 12 (8th October 2014) - Jo, Wan‐Kuen; Park, Gi Tae; Tayade, Rajesh J.
Abstract BACKGROUND The present study focus on the development and feasibility of a blue light emitting diodes (LEDs) source based slurry type spiral‐shaped photocatalytic reactor for degradation of malachite green (MG) dye using P25 Degussa TiO2. The influence of operational parameters such as amount of catalyst loading, initial concentration of dye, and pH of the medium has been studied for optimization of MG dye degradation. RESULTS The photocatalytic degradation of malachite green dye under separate irradiation by blue and by ultraviolet LED was nearly the same (∼76%). The photocatalytic activity using blue LED irradiation was observed due to the synergistic effect of MG dye adsorption on P25 Degussa, which extends the spectral response of TiO2 to the visible region (449 nm). The optimized degradation of 20 mg L‐1 dye was observed at pH 8 using 0.5 g L‐1 of catalyst under irradiation by ultraviolet and blue LEDs for 1 h and 3 h, respectively. CONCLUSION It was found that the synergistic effect of adsorption of malachite green dye on TiO2 surface helped to enhance photocatalytic degradation under blue LED irradiation. The application of a blue LED for photocatalytic degradation of malachite green dye is economical and feasible compared with use of an ultraviolet LED. © 2014 Society of Chemical Industry